2002
DOI: 10.1046/j.1365-2141.2002.03513.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and prognostic characteristics of CD56‐negative multiple myeloma

Abstract: Summary. We analysed CD56 expression in 70 patients with multiple myeloma (MM) to determine its clinicopathological and prognostic significance. Fifty-five (79%) patients were CD56 + . CD56 -patients (n ¼ 15) had higher b 2 microglobulin levels and a higher incidence of extramedullary disease, Bence Jones protein, renal insufficiency and thrombocytopenia than CD56 + patients. Their myelomas more frequently had a plasmablastic morphology. Overall survival was significantly lower in CD56 -than CD56 + patients (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
6
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(122 citation statements)
references
References 9 publications
4
104
6
7
Order By: Relevance
“…3,[20][21][22] Furthermore, we observed that several markers that may be aberrantly expressed in plasma cell neoplasms, CD56, CD10 and CD4, were also expressed in most cases of plasmablastic lymphoma. CD56 and CD10, markers frequently expressed in plasma cell myeloma, [23][24][25] were positive in 5/9 and in 6/9 of the plasmablastic lymphoma cases in our series, respectively. Given the preponderance of post-germinal center markers seen in all of our plasmablastic lymphoma cases, we believe that CD10 expression in plasmablastic lymphoma is temporally aberrant, as may be seen in plasma cell myeloma.…”
Section: Discussionsupporting
confidence: 49%
“…3,[20][21][22] Furthermore, we observed that several markers that may be aberrantly expressed in plasma cell neoplasms, CD56, CD10 and CD4, were also expressed in most cases of plasmablastic lymphoma. CD56 and CD10, markers frequently expressed in plasma cell myeloma, [23][24][25] were positive in 5/9 and in 6/9 of the plasmablastic lymphoma cases in our series, respectively. Given the preponderance of post-germinal center markers seen in all of our plasmablastic lymphoma cases, we believe that CD10 expression in plasmablastic lymphoma is temporally aberrant, as may be seen in plasma cell myeloma.…”
Section: Discussionsupporting
confidence: 49%
“…Several studies have shown association between the absence of expression in MM patients and extramedullary myeloma and shorter PFS but not different OS [20][21][22]. We also confirm that there is no prognostic impact of CD56 on MM patients' OS.…”
supporting
confidence: 83%
“…Although it was suggested that downregulation of CD56 (NCAM) by aberrant PC is involved in extramedullary spreading, an increased aggressiveness and adverse outcome in MM (75)(76)(77), this has not been confirmed by others (78,79) and in fact, lack of CD56 expression has been associated with fewer osteolytic lesions (68,69). Similarly, CD45 expression has also been claimed to be associated with increased PC proliferation, due to the potential role of the CD45 tyrosine phosphatase on the expression of both the IL-6 and IGF-1 PC growth factor receptors (36).…”
Section: Utility Of Mfc In MM and Other Plasma Cell Dyscrasiasmentioning
confidence: 99%